2003
DOI: 10.1167/iovs.02-0716
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring Retinal Function during Transpupillary Thermotherapy for Occult Choroidal Neovascularization in Age-Related Macular Degeneration

Abstract: fERG amplitude decreases transiently during TTT, despite the absence of ophthalmoscopically apparent lesions. Intraoperative amplitude depression may result from an adaptation effect to laser light energy and/or hyperthermia, resulting in desensitization of cone photoreceptors and bipolar cells. Treatment sites are electrophysiologically functional 1 month after TTT. Detailed parametric study of a larger patient group is needed to determine whether fERG testing is potentially useful for monitoring and perhaps … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
(53 reference statements)
0
13
0
Order By: Relevance
“…They based their method on the subjective functional findings of Mayer and associates, 47 who found that affected low and midtemporal frequencies were associated with funduscopic features in early ARM. In addition, the focal ERG has been successfully applied to document effects of treatment after transpupillary thermotherapy in occult neovascular ARM 48 and after short term antioxidant supplementation in subjects with early ARM. 49 While the focal ERG is useful in documenting age-related maculopathy, the application is restricted to one area and it does not allow a mapping of many areas within the posterior pole.…”
Section: Full-field and Focal Electrophysiological Assessment In Armmentioning
confidence: 99%
“…They based their method on the subjective functional findings of Mayer and associates, 47 who found that affected low and midtemporal frequencies were associated with funduscopic features in early ARM. In addition, the focal ERG has been successfully applied to document effects of treatment after transpupillary thermotherapy in occult neovascular ARM 48 and after short term antioxidant supplementation in subjects with early ARM. 49 While the focal ERG is useful in documenting age-related maculopathy, the application is restricted to one area and it does not allow a mapping of many areas within the posterior pole.…”
Section: Full-field and Focal Electrophysiological Assessment In Armmentioning
confidence: 99%
“…However, the higher temperature will also spread to the sensory retina and induce damage leading to a decrease in the FMERGs. An earlier study reported that the amplitudes of the focal ERGs decreased transiently after TTT in spite of the absence of ophthalmoscopic changes of the fundus [21]. However, the impairment of retinal function is temporary, and longer follow-up studies at 3 and 6 months are necessary to determine the final effect of TTT on the focal ERGs.…”
Section: Discussionmentioning
confidence: 98%
“…Treatment was performed with one spot of 60 seconds duration at a variable power setting of 400−600 mW, such that no visible change of the lesion was detected throughout the treatment. The choice of power setting for an individual eye was based on a combination of parameters, including VA, and iris and fundus pigmentation, according to a published protocol (Falsini et al 2003).…”
Section: Methodsmentioning
confidence: 99%
“…Possible mechanisms include thermally induced changes in ocular blood flow, selective damage to endothelial cells of abnormal choroidal new vessels through hyperexpression of heat shock proteins, and subthreshold activation of RPE cells (Samali & Orrhenius 1988; Beckmann et al 1990; Mainster & Reichel 2000; Ciulla et al 2001; Desmettre et al 2001). The effects of TTT on retinal function are a matter of investigation (Falsini et al 2003). While some studies suggest an efficacy of treatment on CNV, it is still unknown whether, and to what extent, the neurosensory retina undergoes changes as a result of TTT.…”
Section: Introductionmentioning
confidence: 99%